Imagem corporal e somatotipo: investigações em população de mulheres universitárias - Castro, Marcela Rodrigues de [UNESP] (2014)
This study aimed to understand the associations between somatotypical profile and body image from a multidimensional approach, in which we include perceptual and attitudinal dimensions. We sought to verifying whether the psychometric qualities of instruments assessing dissatisfaction and body perception with a focus on real image of the subject, dynamic image and somatotype (Escala de Silhuetas do Próprio Sujeito- ESPS, Escala de Silhuetas Baseadas no Somatotipo - ESBS, Imagem Dinâmica do Corpo - IDC). The sample included 142 undergraduate female students (21.81 ± 3.014 years) who underwent to assessment of Body Mass Index and somatotype, according to the World Health Organization and Heath-Carter protocols, respectively. To assess the attitudinal dimension we applied the instruments: Body Shape Questionnaire, Body Attitudes Questionnaire, Body Image Avoidance Questionnaire, Sociocultural Attitudes Towards Appearance Scale, Self Subject Silhouettes Scale (ESPS) and Silhouettes Based on Somatotype Scale (ESBS). To measure perceptual dimension 3 psychophysical tasks were used: ESPS, Estimation of Magnitude and Estimation of Category. This last one was performed in two conditions: own body image and body of the 4 unknown models. We performed descriptive analysis using measures of central tendency, dispersion, relative and absolute frequency. To verify the association between categorical variables we performed Chi-square test. To verify the normality of continuous data we proceeded to Shapiro-Wilk test (p<0.05). We applied multivariate statistical variance (one-way MANOVA) for variables that showed normal distribution. We applied the Kruskal- Wallis test for analysis of variance to the results which were not normally distributed. To verify the association between variables we applied the Mann-Whitney test for independent samples and Spearman correlation. The ESPS, ESBS and IDC scales were considered valid, reliable and stable tools to...